+0  
 
0
48
3
avatar

1. Consider the polynomial \(p(x) = x^3 + (1-i)x^2 + 2i x + 3+4i.\)Calculate \(p(1), p(i),  p(1+i), p(1-i)\).

 

2. Consider the polynomial \(p(z) = z^3 +2z^2 - z + 4.\)Calculate \(p(2+i), p(2-i), p(1+3i), p(1-3i)\).

 

3. Let p be a polynomial with real coefficients such that \(p(1-2i) = 1+3i \text{ and } p(3+4i) = 2 - i.\)Calculate \(p(1 +2i), p(2+4i), p(3-4i)\)if any of these are not uniquely determined, enter ? for that value.

 

Could someone help me with these please? Thanks!

 Feb 23, 2020
 #1
avatar+109450 
+1

1.     Remember  that  i^2  = -1       i^3   =  -i        i^4    =1

 

P(1)  =   (1)^3  + (1 - i)(1)^2  + 2i(1)  + 3 +4i

                =     1   + 1   - i  + 2i  +  3 + 4i

                =      5  +  5i

 

P(i)  = (i)^3 + (1  -i)(i)^2  + 2i(i)  + 3 + 4i

        =  -i   + (1 - i)(-1)  + 2i^2  + 3 + 4i

        =  -i  - 1 + i  + 2(-1) +  3  +  4i

        =     -1   -   2  + 3   +  4i

        =    4i

 

P(1 + i)  =  (1 + i)^3  + (1 - i) (1 + i)^2  + 2i (1 + i)  +  3  + 4i

                Note  that we can write

                 ( 1 + i)  [ (1 + i)^2  +  (1 - i) ( (1 + i)  + 2i ]  +3 + 4i     =

                 (1 + i)  [ (1 + 2i +i^2  + 1  - i^2  + 2i   ] +  3 + 4i  =

                 (1 + i)  [ 1  + 2i  - 1  + 1  + 1  + 2i ]  + 3  + 4i   =

                 (1 + i)  [ 2 + 4i)  + 3 + 4i =

                  (2  + 2i + 4i + 4i^2) + 3 + 4i  =

                  (2  + 6i - 4 ) + 3 + 4i  =

                   (6i - 2) + 3 + 4i  =

                    1 + 10i

 

P(1 - i)  =  (1 - i)^3  + (1 - i)(1 - i)^2  + 2i (1 - i) + 3  + 4i

                And we can write

                (1 - i)  [ (1 - i)^2  +(1 - i)^2  + 2i ]  + 3  + 4i  =

                ( 1 - i)  [ 1  - 2i + i^2  + 1 - 2i  + i^2  + 2i ] + 3 + 4i   =

                (1 - i)  [ [ 1  - 2i  - 1  + 1  -2i  -1  + 2i ] + 3 + 4i   =

                (1 - i) [ -2i]  + 3 + 4i    =

                 -2i  + 2i^2  + 3  + 4i  =

                  -2i  - 2 + 3  + 4i   =

                   1  +  2i

 

 

cool cool cool

 Feb 23, 2020
 #2
avatar+109450 
+1

2.

p(2 + i)   = (2 + i)^3  + 2(2 + i)^2  - (2 + i)  + 4

              =  (2 + i )  [  (2 + i)^2  + 2 (2 + i) - 1 ] + 4

              =  (2 + i)  [ 4 + 4i + i^2  + 4  + 2i  - 1  ] + 4

              =  (2 + i) [ 4 + 4i  - 1  + 4  + 2i  - 1  ]+ 4

             =  (2 + i) [ 6 + 6i ] + 4

              =    12 + 6i + 12i  + 6i^2  + 4

              =    12  + 18i  - 6  + 4

               =    10 + 18i

 

P(2 - i)  =  (2 - i)^3  + 2(2 - i)^2  - (2 - i)  + 4

             =  (2 -i)  [ (2 - i)^2  + 2(2 -i) - 1  ] +  4

             =  (2 -i)  [ 4  - 4i  + i^2  + 4 - 2i - 1  ] + 4

            =  ( 2 -i) [ [ 4  - 4i   - 1  + 4  - 2i  - 1  ]  + 4

             =  ( 2  - i) [ 6 - 6i ] +  4

             =   12 - 6i - 12i  + 6i^2  + 4

              =   12  - 6i  - 12i  - 6 +  4 

              =   10  - 18i

 

P(1 + 3i)  =  (1 + 3i)^3  + 2(1 + 3i)^2  - (1 + 3i)  + 4

                =  ( 1 + 3i) [ ( 1 + 3i)^2  + 2(1 + 3i) - 1  ] + 4

               = (1 + 3i)  [ 1 + 6i + 9i^2 + 2 + 6i - 1 ] + 4

               =  (1 + 3i) [ 1 + 6i - 9 + 2 +6i - 1  ]+ 4

                 = ( 1 + 3i)  [ 12i -7 ] + 4

                 = ( 12i + 36i^2 - 7 - 21i)  + 4

                 =  ( -9i - 36 - 7 ] + 4

                  = - 39  - 9i

 

Note  that   P(2 + i)  and P(2 - i)   only differed by signs  on  the  "i"  term

 

So....we would expect that  P( 1 - 3i)    would  just be    -39 + 9i

 

cool cool cool

 Feb 23, 2020
 #3
avatar+109450 
+1

3.

 

From the results  in   (2)   we  would expect  that

p(1 + 2i)  =  1 - 3i       and

p(3 - 4i)  =  2  + i

 

p ( 2 + 4i)    =    ?      (cannot  be  determined  )

 

 

cool cool cool

 Feb 23, 2020

14 Online Users

avatar
avatar